(untitled) (International Journal of Communication Systems and Network Technologies, 2020)
Due to the gradual increase of Internet users, the main problem arises as duplicity and copying that led to content integrity and protection. We need some techniques to handle/secure the speech signals from an illegitimate user of digital content. These issues can be solved using speech watermarking schemes that provide to ensure content authentication and temper recovery. Content authentication is the validation of content integrity. Digital speech watermarking techniques is now in limelight to protecting our speech content from unauthorized copying. In this paper, we have considered the speech watermarking methods along with their important properties. In this paper, we have focused on the theoretical analysis of the important aspects of the forgery. This paper has also included a summary of work on authentication and tamper detection.